URGENSI DAN STRATEGI KONSERVASI WIBAWA HUKUM DALAM MASYARAKAT - M. Akbar (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2019)
Indonesia as a sovereign law state guarantees public order by realizinglegal certainty, fairness and the benefits of established legal products. These threeelements must be realized in the implementation and enforcement of law, so thatthe authority of the law can be felt by the community in increasing awareness andlaw-abiding nature. The principle problem in this study is how to recognize theprotection of human rights which contain the principle of equality before the lawin the life of the community, as well as the quality of legislative legislation in allaspects. The principle of equal treatment before the law is a vital principle inguaranteeing and protecting human rights, insofar as rights and obligations aredeemed balanced and regulated by legislation. Law is present as an intermediary(through a judicial institution) that provides justice for legal subjects who areviolated by their human rights and constitutional rights. This researchrecommends several solutive and constitutional steps as an effort to conserve legalauthority, including; the formulation of appropriate legal legislation, minimizingthe rubber article, having legal certainty, fairness, equal treatment before the law,and effective law.